2021
DOI: 10.1101/2021.01.27.21250570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping a Pandemic: SARS-CoV-2 Seropositivity in the United States

Abstract: Asymptomatic SARS-CoV-2 infection and delayed implementation of diagnostics have led to poorly defined viral prevalence rates. To address this, we analyzed seropositivity in US adults who have not previously been diagnosed with COVID-19. Individuals with characteristics that reflect the US population (n = 11,382) and who had not previously been diagnosed with COVID-19 were selected by quota sampling from 241,424 volunteers (ClinicalTrials.govNCT04334954). Enrolled participants provided medical, geographic, dem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 46 publications
4
34
3
Order By: Relevance
“…A native-like SARS-CoV-2 prefusion stabilized S-2P glycoprotein ectodomain trimer (hereafter referred to as spike) (8,9) has been adopted for large-scale SARS-CoV-2 antigenbased serology and serosurveillance (10)(11)(12)(13). The receptor-binding domain (RBD) located within the more variable S1 subunit of the S glycoprotein, lacking potentially conserved epitopes with endemic seasonal human coronavirus (HCoV) S glycoproteins and conferring specificity for SARS-CoV-2, has also been extensively used in antigen-based immunoassays (10,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…A native-like SARS-CoV-2 prefusion stabilized S-2P glycoprotein ectodomain trimer (hereafter referred to as spike) (8,9) has been adopted for large-scale SARS-CoV-2 antigenbased serology and serosurveillance (10)(11)(12)(13). The receptor-binding domain (RBD) located within the more variable S1 subunit of the S glycoprotein, lacking potentially conserved epitopes with endemic seasonal human coronavirus (HCoV) S glycoproteins and conferring specificity for SARS-CoV-2, has also been extensively used in antigen-based immunoassays (10,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…3 One recent study in a nationally representative sample of U.S. adults found that 4.6% had a history of undiagnosed SARS-CoV-2 as of July 2020: about 5 undiagnosed infections for every diagnosed case. 4…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge of controlling community transmission of SARS-CoV-2 is that the virus’ infectious period allows for onward spread prior to recognition of infection, by the substantial proportion of people with asymptomatic infection, and during the pre-symptomatic period among those who go on to develop symptoms. 4, 5…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologists have conjectured a wide range of possibilities for the degree to which confirmed cases undercount actual cases. A plausible possibility is that the actual number of cases is five times the number of confirmed cases (Kalish et al, 2021), which implies that the actual cumulative number of cases is about 89.5 million. The size of the American population is about 331 million.…”
Section: Optimal Constrained Choice Between Mandate and Decentralizationmentioning
confidence: 99%
“…Confirmed cases undercount actual cases to an unknown degree. A plausible possibility is that the actual number of cases was five times the number of confirmed cases(Kalish et al, 2021). If so, the actual number of new cases per day was 1,080,350.…”
mentioning
confidence: 99%